Bringing it all together: a multi-method evaluation of Tanum 247:1 - Potter, Rich; Horn, Christian; Meijer, Ellen (Danish Journal of Archaeology, 2022)
This paper presents the results of a photogrammetric survey of the rock art panel Tanum 247:1 in Kalleby, which revealed an entirely new boat that had previously been missed in a documentation history over 50 years long. Through the combined use of digital and traditional methods the results could be verified. It is therefore argued that collating documentations, both past and present, can help to create a better picture of Bronze Age rock art carvings. In addition to using new and traditional documentation methods together, panels should be recorded beyond what is known, both in terms of discovering unknown carvings, as well as creating better data for future researchers.